Close Observation of Mother-Infant Interactive Process in the Wake of Traumatic Loss: The September 11, 2001 Primary Prevention Project. Issue 3 (2nd September 2021) - Beebe, Beatrice; Sossin, K. Mark; Cohen, Phyllis; Moskowitz, Sally; Reiswig, Rita; Tortora, Suzi; Demetri Friedman, Donna
Abstract : The 20th anniversary of the World Trade Center (WTC) disaster is a powerful moment in our history. We feel honored to be invited by Rachel Altstein to participate in this issue of Psychoanalytic Perspectives. In the current paper, we take a retrospective look at some early work we did with the women who were pregnant on September 11, 2001, when they were tragically widowed as the towers fell. We offer close observation of interactive process in two dyads at infant age four months in order to try to understand more about mother-infant interaction in the context of traumatic grief and loss. We narrate a descriptive story of the interactive process based on viewing the films of face-to-face interactions, first in real-time, followed by slow-motion video, followed by frame-by frame viewing in some sections. Because human face-to-face communication is so rapid, complex, and subtle, it is impossible to see the nuances of communication in real time. As the working group of The September 11, 2001 Primary Prevention Project, we viewed the videos together many times and gradually, through discussion, reflection and review, generated a narrative that represents our clinical view.